2003
DOI: 10.1074/jbc.m210184200
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Proteomic Analysis of Breast Cancer Cell Membranes Reveals Unique Proteins with Potential Roles in Clinical Cancer

Abstract: Proteins associated with cancer cell plasma membranes are rich in known drug and antibody targets as well as other proteins known to play key roles in the abnormal signal transduction processes required for carcinogenesis. We describe here a proteomics process that comprehensively annotates the protein content of breast tumor cell membranes and defines the clinical relevance of such proteins. Tumor-derived cell lines were used to ensure an enrichment for cancer cell-specific plasma membrane proteins because it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
167
1
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(179 citation statements)
references
References 26 publications
10
167
1
1
Order By: Relevance
“…Previously, S100A14 was identified as a plasma membrane-associated protein in breast cancer cell lines and exhibited an increased expression in breast cancer tissues versus matched normal tissues. Accordingly, S100A14 exhibited different patterns of subcellular distribution, typified by plasma membrane localization in breast cancer tissues but cytosolic expression in nontumor breast epithelial cells (35). Previous studies showed that some members of the S100 family of proteins exhibit calcium-dependent translocation (36,37), and the translocation of S100A14 is regulated in a calcium-dependent manner through interaction with nucleobindin, which has strong association with Ga proteins (38).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, S100A14 was identified as a plasma membrane-associated protein in breast cancer cell lines and exhibited an increased expression in breast cancer tissues versus matched normal tissues. Accordingly, S100A14 exhibited different patterns of subcellular distribution, typified by plasma membrane localization in breast cancer tissues but cytosolic expression in nontumor breast epithelial cells (35). Previous studies showed that some members of the S100 family of proteins exhibit calcium-dependent translocation (36,37), and the translocation of S100A14 is regulated in a calcium-dependent manner through interaction with nucleobindin, which has strong association with Ga proteins (38).…”
Section: Discussionmentioning
confidence: 99%
“…Preparation of membrane fractions and mass spectrometry on a 20 cm 6% Laemlli one-dimensional gel (BioRad, Hemel Hempstead, UK) and 0.5 mm slices were subjected to trypsinolysis and prepared for MALDI-TOF mass spectrometry (Voyager STR, Applied Biosystems, Framingham, MA, USA) as previously described (Adam et al, 2003). Selected peptide masses for CD70 (M þ H) ¼ 1217.6 and 1142.6 were characterised further by MS/MS using a tandem quadrupole TOF mass spectrometer equipped with a nanospray ion source (Micromass UK Ltd, Manchester, UK).…”
Section: Methodsmentioning
confidence: 99%
“…To compile a list of candidate RCC cell-surface proteins, we used a previously described proteomics approach adapted for breast cancer cell lines (Adam et al, 2003) using plasma membrane preparations from the A498, SW839 and CAKI-2 RCC-derived cell lines. As described previously (Adam et al, 2003), potential targets were analysed further using real-time quantitative RT -PCR and immunohistochemistry to quantify expression in normal tissues and clinical RCC samples.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 The oligonucleotide primer sequences (Invitrogen, Carlsbad, CA, USA) were derived from a previous paper 15 as shown in Table 1. For RT-PCR of MART-1 mRNA, the forward primer, 5 0 -CACGGCCACTCTTACAC CAC-3 0 , and the reverse primer, 5 0 -GGAGCATTGG GAACCACAGG-3 0 , yielded a product of 254 bp.…”
Section: One-step Rt In Situ Pcrmentioning
confidence: 99%